Midterm Results of a Minimally Invasive Approach in David Procedure - Monsefi, Nadejda; Risteski, Petar; Miskovic, Aleksandra; Moritz, Anton; Zierer, Andreas (The Thoracic and Cardiovascular Surgeon, 2018)
Background The David procedure is a well-known technique in selected patients with aortic root pathology. A minimally invasive approach in heart surgery increases open interest.Methods From 1991 to 2015, the David technique was performed in 296 patients in our unit. In 90 cases, operations were performed through partial upper sternotomy. The patient mean age was 57 ± 14 years in the minimally invasive group (n = 90) and 58 ± 14 years in the complete sternotomy group (n = 206; p = 0.2). The neosinus modification was performed in 80 patients (89%) in the minimally invasive group and in 79 patients (38%) in the complete sternotomy group (p < 0.01). Mean follow-up was 3 ± 2 years in the minimally invasive group and 8 ± 4 years in the complete sternotomy group.Results Thirty-day mortality was zero in the minimally invasive group and was 3% (n = 6) in the complete sternotomy group (p = 0.1). The need for packed red blood cells was significantly lower in the minimally invasive group (1.6 ± 3 U) than in the complete sternotomy group (3.7 ± 6 U; p < 0.01). Thirty late deaths (2% per patient-year) were observed in the complete sternotomy group versus zero in the minimally invasive group (p < 0.01). One patient (0.5% per patient-year) in the minimally invasive group and 12 patients (0.8% per patient-year) in the complete sternotomy group required reoperation in the follow-up period (p = 0.05).Conclusions Minimally invasive David technique for patients with ascending aortic aneurysm and aortic valve insufficiency offers a good solution with low perioperative blood transfusion rate. Our midterm results show low valve-related complications and reoperation rate. However, long-term follow-up of the minimally invasive group is necessary.
Keywords: aortic valve and root; heart valve surgery; minimally invasive surgery